2010
DOI: 10.1002/mabi.201000245
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the Differentiation Niche of Embryonic Stem Cells Using Biomaterials

Abstract: The biochemical cues and topographical architecture of the extracellular environment extensively influence ES cell fate. The microenvironment surrounding the developing embryo presents these instructive cues in a complex and interactive manner in order to guide cell fate decisions. Current stem cell research aims to reconstruct this multifaceted embryonic niche to recapitulate development in vitro. This review focuses on 2D and 3D differentiation niches created from natural and synthetic biomaterials to guide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 174 publications
(204 reference statements)
0
39
0
Order By: Relevance
“…ESCs have garnered much attention as a source of cells for regenerative therapies due to their almost indefinite self-renewal capacity in culture and their robust differentiation into all cell types. Nonetheless, to maintain karyotypically stable ESC cultures, it is necessary to grow them on embryonic fibroblasts or some other extracellular microenvironment [50], demonstrating their niche requirement in vitro .…”
Section: Diversity Of the Stem Cell Nichementioning
confidence: 99%
“…ESCs have garnered much attention as a source of cells for regenerative therapies due to their almost indefinite self-renewal capacity in culture and their robust differentiation into all cell types. Nonetheless, to maintain karyotypically stable ESC cultures, it is necessary to grow them on embryonic fibroblasts or some other extracellular microenvironment [50], demonstrating their niche requirement in vitro .…”
Section: Diversity Of the Stem Cell Nichementioning
confidence: 99%
“…Biomaterials based on components of the ECM may direct differentiation of pluripotent stem cells towards different lineages (Table V) (Dickinson et al, 2011). Besides serving as structural support, the ECM provides biochemical and mechanical signals to the cells, mainly mediated by integrins, which helps control cell fate (Eshghi and Schaffer, 2008 (Wary et al, 1996).…”
Section: Interaction Of Biomaterials With Cellsmentioning
confidence: 99%
“…ECM provides nanoscale structures, such as the 15-300 nm in diameter collagen fibrils that allow cell adhesion (via integrins) and immobilization of signaling molecules, thus influencing the fate and behavior (i.e., proliferation, migration and differentiation) of stem cells [107]. The concentration, size, spacing, surface chemistry and shape (e.g., ridges, grooves, pores and pits) of the artificial nanostructures (e.g., nanotubes and nanolines) are important parameters for the development of cell adhesion sites that monitor stem cell behavior [108][109][110]. For example, it has been shown that surface irregularity (e.g., nanoline grating) and diverse surface chemistries (e.g., silica and poly[methyl methacrylate]) are capable of enhancing adhesion, alignment, growth and differentiation of stem cells [108,109].…”
Section: A U T H O R P R O O Fmentioning
confidence: 99%